VD_FINDINFO HC / 2009 / 70 vom 6. April 2009 - VD Tribunal cantonal (2009)
SUSPENSION DE LA PROCÉDURE, NULLITÉ, VENTE, LÉSIONDROIT DES OBLIGATIONS, ERREUR ESSENTIELLE | 20 CO, 21 CO, 24 al. 1 ch. 3 CO, 123 CPC, 452 CPC, 465 al. 1 CPC, 471 al. 3 CPC